2008
DOI: 10.1152/ajpregu.00162.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and metabolic rhythms associated with the daily scheduled nursing in rabbit pups

Abstract: Young rabbits are nursed every 24 h for a period of 3-5 min. As a consequence, pups are synchronized to this nursing event; this synchronization is characterized by increased locomotor activity and a peaking of core temperature and plasma corticosterone in anticipation of the daily meal. Ghrelin is a hormone suggested to play a role in meal initiation and to promote food intake. The present study explored the role of ghrelin in food-entrained conditions. Newborn rabbits were maintained in constant darkness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
51
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 31 publications
12
51
2
Order By: Relevance
“…Additionally, at this age, their circadian visual system is immature (Juárez et al, 2013) and the SCN is not necessary for food entrainment (Hernández-Campos et al, 2011). Accordingly, the synchronization of FAA and some brain structures shifts in parallel when nursing is scheduled either during the day or the night (Caba et al, 2008;Morgado et al, 2008Morgado et al, , 2010a, as well as the telencephalic regions of the present contribution, as indicated by PER1 protein, product of the Per1 clock gene in preliminary experiments (Moreno et al, 2012;Morgado et al, 2010b). Hence, the effects observed in the three telencephalic areas are indeed due mainly to ingestion of food and not to an influence of the SCN.…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, at this age, their circadian visual system is immature (Juárez et al, 2013) and the SCN is not necessary for food entrainment (Hernández-Campos et al, 2011). Accordingly, the synchronization of FAA and some brain structures shifts in parallel when nursing is scheduled either during the day or the night (Caba et al, 2008;Morgado et al, 2008Morgado et al, , 2010a, as well as the telencephalic regions of the present contribution, as indicated by PER1 protein, product of the Per1 clock gene in preliminary experiments (Moreno et al, 2012;Morgado et al, 2010b). Hence, the effects observed in the three telencephalic areas are indeed due mainly to ingestion of food and not to an influence of the SCN.…”
Section: Discussionmentioning
confidence: 81%
“…Seymour Levine, one of the first to study the role of early experiences in shaping stress responses, has left a lasting legacy regarding the profound influence of the mother on the development of the stress system in numerous species (Levine, 1957, 1967; Lyons, Martel, Levine, Risch, & Schatzberg, 1999; Morgado et al, 2008; Schmidt et al, 2006; Stanton et al, 1987). The data outlined in this review indicate that functional changes in infant learning are modified by a unique interaction between the developing CORT system, the amygdala, and the learning context that depends on whether the mother is present or absent.…”
Section: Discussionmentioning
confidence: 99%
“…These behavioral and physiological parameters synchronized with mealtime are controlled by a putative food-entrainable oscillator (FEO; Stephan, 2002). Recently, we reported that Cort and free fatty acids (FFA) also seemed to be entrained by nursing scheduled at 10:00 h, in rabbit pups housed in constant dark conditions, but whose mothers were exposed to a 12h:12h light/dark cycle with lights on at 07:00 h. On the contrary, stomach weight and liver glycogen followed an exogenous rhythm as values increased only after nursing, but not in fasted pups (Morgado et al, 2008). In the same study, we also found that ghrelin was low at nursing and reached a peaked 12 h later, whereas this pattern was absent in fasted pups.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in rats and humans, the physiological consequences of food ingestion are critically dependent of the time of day at which feeding takes place (Belda et al, 2005; Goel et al, 2009; Yoshihara et al, 2005). In our previous study in the rabbit, pups were scheduled to suckle during the day, at 10:00 h (Morgado et al, 2008). However, rabbits mothers nurse their pups during the night, at around 02:00 h (González-Mariscal et al, 2009; Jilge, 1991, 1993; Szeto et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation